Organization and Design of Development of Islamic Religious Education in Indonesia - Yoespie Arief Amirullah; Tasman Hamami (At-Ta'dib, 2020)
This article discusses the organization and design of curriculum development in Indonesia. It discusses the elements of education concerning the development of character in Indonesia. So in developing an educational curriculum in Indonesia it is necessary to evaluate a targeted education curriculum in line with the learning methods of students. Such as the boredom experienced by students while learning in the class. And the lack of teacher preparation in teaching makes the curriculum function role not run optimally. Special theories are required and has been needed for developing the method and learning out come in the Islamic Education curriculum design. The purpose of this study, to find out firsthand the process of implementing the curriculum in Indonesia, especially about the Islamic education curriculum. Then from the aim of this research, it is hoped that it can help in developing the organization and curriculum design of PAI in Indonesia. For this reason, the curriculum in Indonesia needs to be designed with development and direction in the challenges of the globalization era. To achieve this, students, teachers, and students need to appreciate by creating a curriculum that can facilitate the course of Islamic education in Indonesia. This research method, using library research. The author thoroughly discusses the organizational problems and design of the development of the curriculum Islamic education in Indonesia. The author also approaches by referring to various scientific studies of journal sources. The results of this study, that the organization and design of the Education curriculum are very influential in student development. Also, in developing the design organization Islamic education  curriculum development in Indonesia is expected to be able to compete nationally and internationally.